English Education During the Pandemic - From Face to Faceless - Promnitz-Hayashi, Lara (KnE Social Sciences, 2022)
Covid-19 has changed education as we know it. What we thought would be a temporary challenge has turned into what feels like an endless one. In 2020, education systems around the world were thrown into what could easily be classified as ‘chaos’. Many countries have seen education sectors shut down completely due to non-existent infrastructure to provide classes outside the physical classroom. While this is understandable in less developed countries, insufficient emergency remote education infrastructure in advanced countries is extremely surprising and disappointing. Some countries have had success though and been able to deliver education in alternative ways. The spread of Covid-19 saw tertiary institutions across Japan turn to emergency online learning; however, many were not prepared for this. Institutions do not always have sufficient online resources, and educators and students alike may not have technological proficiency, which hinders the learning experience. 2021 has seen a continuation of the pandemic and while some Japanese universities have continued to present lessons either online or on-demand, many have returned to the physical classroom. Face-to-face classes are not the same as pre-Covid-19. While students may be more content to see their classmates and teachers, there are numerous challenges that arise which can still hinder not only the learning process, but also the social aspect in class, as there are strict protocols which need to be adhered to and teachers must adapt their lessons to accommodate these. This research will discuss the positive and negative aspects of online classes in 2020, and compare them to the return to face-to-face classes in 2021. A number of activities undertaken in both formats will also be discussed. Keywords: education in the time of Covid-19, computer-assisted language learning, online teaching methodology